2023
DOI: 10.3390/ma16237423
|View full text |Cite
|
Sign up to set email alerts
|

Annealing Heat Treatment for Homogenizing the Microstructure and Mechanical Properties of Electron-Beam-Welded Thick Plate of Ti-6Al-4V Alloy

Seongji Seo,
Jiyong Park

Abstract: In the application of Ti-6Al-4V to aerospace structural components, when welding thick plates similar of the thickness of the components, microstructure and hardness gradients emerge between the base material (BM) and the joint. This leads to the issue of significant stress concentration in the BM under tensile stress. To address this problem through post-welding heat treatment, this study conducted heat treatments at temperatures both below (mill annealing, MA) and above the beta-transus temperature (beta ann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…Centrifugal casting Ti-6Al-7Nb alloy under investigation in this work was formed into a rod. A vacuum electric arc furnace was used to melt wrought Ti-6Al-7Nb rod [31]. A rod was created by casting the molten metals.…”
Section: Centrifugal Casting Materials and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Centrifugal casting Ti-6Al-7Nb alloy under investigation in this work was formed into a rod. A vacuum electric arc furnace was used to melt wrought Ti-6Al-7Nb rod [31]. A rod was created by casting the molten metals.…”
Section: Centrifugal Casting Materials and Methodsmentioning
confidence: 99%
“…Meanwhile, primary α (α p ) and secondary α precipitation (α s ) in titanium alloys are required to achieve perfect strength-plasticity matching and increased corrosion resistance. In addition, coarse columnar grains can be changed to become more homogeneous with solution treatment and aging (STA), thereby increasing the corrosion resistance of the Ti-6Al-4V alloy [31].…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…Solution plus single aging was usually used by some researchers who found that the α p phases are highly sensitive to the Materials 2024, 17, 570 2 of 15 solution temperature, while the α s phases are greatly affected by aging conditions [16,22]. Moreover, the precipitation of α s phases could significantly enhance the properties of Ti alloys [28][29][30]. Shaha et al [31] reported fine α phases and low residual stress in the Ti55511 alloy, resulting in improved mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
“…Ti-6Al-4V (TC4) alloy, as a two-phase ( α + β ) titanium alloy, displayed remarkable structural stability, excellent mechanical properties, high plasticity, toughness, and resistance to high-temperature deformation [ 1 , 2 , 3 ]. Due to these characteristics, the TC4 alloy was extensively applied in various areas, such as compressor blades and impellers of jet engines, landing gear wheels, aircraft accessories, and pipes [ 4 , 5 , 6 ]. Various complex TC4 alloy parts were commonly fabricated through methods such as casting, forging, and machining [ 7 , 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%